TERAPI DISTRAKSI AUDIOVISUAL MENURUNKAN NYERI PERUT PADA ANAK DENGAN GASTROENTERITIS AKUT (GEA): TERAPI DISTRAKSI AUDIOVISUAL MENURUNKAN NYERI PERUT PADA ANAK DENGAN GASTROENTERITIS AKUT (GEA) - Nova Pangesti; Dina Indra Puspitasari (STIKES Pemkab Purworejo, 2023)
Background: Acute gastroenteritis (GEA) is an endemic disease that has the potential to become an extraordinary event (KLB) and is often accompanied by death. The problem that arises in acute gastroenteritis in children is acute pain in the abdominal area due to increased bowel sounds. One of the appropriate therapies that can be given to children with abdominal pain is audiovisual distraction therapy. Audiovisual distraction therapy is diverting children's attention to things that are popular in this study using upin and ipin cartoon videos. Objective: to determine the implementation of audiovisual distraction therapy in reducing abdominal pain in children with acute gastroenteritis (GEA). Method: The research used was a case study with two child clients with a medical diagnosis of acute gastroenteritis who experienced acute pain nursing problems aged 3-6 years. Results: There is an effect of giving audiovisual distraction therapy for 15 minutes to pediatric acute gastroenteritis patients on a decrease in client 1's pain scale from very painful to not painful, client 2 from very painful to not painful. Conclusion: Based on the research that the authors have done, it shows that after audiovisual distraction therapy is effective in reducing the pain scale in both clients with the result from very painful to not painful.